O personal learning environment como uma possibilidade de aprendizagem na WEB 2.0 - Lamattina Júnior, Paulo (2010)
The intention of the paper The Personal Learning Environment as a possibility of learning in the WEB 2.0 is to explore the possibilities of use of new technologies in learning processes. Due to the fact that, time wise, the technology became more affordable to a biggest group of people and that every day more and more people that come into the scholar age are familiar with its use, we tried to identify how this new generation uses these tools in their learning processes. Specially, we have studied the PLE Personal Learning Environment that enables the aggregation of several different tools and resources available in the WEB 2.0, making possible the electronic register of the virtual ways that each individual goes through. The theoretical part was supported by some different authors. From Santaella we lend the considerations of the immersive reader in the virtual universe, from Piaget and Ausubel we will bring the subsidies to comprehend the bases to the collaborative learning. Thus, this paper intends to connect the learning theories to the every day more intensive use of technology together with the new possibilities of learning using the WEB 2.0, having in mind that the new students are familiar with its potential and know how to use them